Fire danger analysis of seismic expansion joints - Inomzhon U Madzhidov; Bahrom T Ibragimov; Adiljan A Suleymanov (Structural Mechanics of Engineering Constructions and Buildings, 2019)
Aim of the research. Investigation of fire danger of seismic expansion joints, which have recently become almost the main component of seismic protection of buildings and structures. Identify the degree of fire danger of the building structure. Develop preventive measures to ensure fire safety of buildings and structures where seismic expansion joints are used. The relevance of this problem lies in the fact that the destruction of deformation seismic joints in seismic conditions for the spread of combustion (usually secondary occur in earthquakes) from one compartment of the building to another (protected by partitions, fire compartments, locks). That is, combustion opens the possibility to bypass special protections put in its way, in order to avoid its spread. Methods. Antiseismic deformation joints have been studied from the point of view of fire safety. The work mainly deals with the expansion joints used in the installation of aluminum panels for the design of buildings and structures. The connection of fire danger of antiseismic joints combined with technological and operational errors of performers is shown. Tests of various seismic protection joints for fire danger have been carried out. Results. It is concluded that it is necessary to develop a special regulatory documentation that introduces specific rules for the execution of expansion joints, especially designed to improve the seismic safety of buildings and structures.